Comparison of roughness index for Kitka and Koznica wind farms - Bukurije Hoxha; Bedri Dragusha (Institute of Advanced Engineering and Science, 2021)
Kosovo has limited renewable energy resources and its power generation sector is based on fossil fuels. Such a situation emphasizes the importance of active research and efficient use of renewable energy potential. According to the analysis of meteorological data for Kosovo, it can be concluded that among the most attractive potential wind power sites are the locations known as Kitka (42° 29' 41